Efektivitas Metode Resitasi Dalam Konsep Pendidikan Islam Perspektif Peserta Didik Abad 21 - Mohammad Faizin; Novi Aghata Nur Khamalia; Nur Elvinatuz Zuhroh; Anna Fadhilah Pitaloka (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
The success of the learning process can be seen from the learning outcomes. Educators have an important role in this success. In addition, the application of learning methods is one of the factors that influence learning outcomes. One method that can be applied in the learning process in the 21st century is the recitation method. This method can train students to think more actively. The application of the recitation method also has stages that must be passed so that the learning process gets good and perfect results. One of the advantages of applying this method in the learning process is that students become more active, more independent, and have the courage to take responsibility. However, the application of this method also has drawbacks, one of which is the frequent occurrence of fraud in carrying out the assigned tasks. Not infrequently students choose alternatives to plagiarize the work of others.